APLIKASI PEMESANAN LAPANGAN FUTSAL ONLINE BERBASIS ANDROID (STUDI KASUS : PUTRA FUTSAL BUMIAYU) - Giris prasetyo budi; Fathulloh .; Fuaida nabyla (Informatika Publisher, 2020)
Futsal is a sport that is very popular in Indonesia. In addition to a good field, a good field rental system is also a factor in consideration for tenants choosing futsal field rentals. Ordering and collecting data on Bumiayu Putra Futsal which is still manual will make the length of the process of recording and searching for information, as well as ordering systems that have to be face-to-face and come directly to a certain place will take a lot of time to do so. This can of course waste consumers' time, costs and power. Based on these problems the authors intend to build an information system that makes it easier for consumers and managers to get information about field schedules and futsal field orders. In building a futsal field ordering system the writer uses the waterfall method. Data collection techniques using observation, interviews, and library research program implementation used is the Android programming language. Based on the results of the analysis and discussion, the online futsal field ordering system can be accessed anytime and anywhere. In this system includes information on field schedules, and futsal field bookings, this system was built intended to provide facilities for futsal field owners to publicize their futures sites.